Food and Nutrition Insecurity in Venezuelan Migrant Families in Bogotá, Colombia - Pico, Rocio; del Castillo Matamoros, Sara; Bernal, Jennifer (Frontiers in Sustainable Food Systems, 2021)
Venezuela has had the largest migration in recent history, with 4.8 million people displaced due to sociopolitical, economic, electrical blackouts, and health crises. Nine out of ten migrants are facing food insecurity during the COVID19 pandemic. Colombia has received the largest number of Venezuelan migrants, counting officially 1,764,883 to date. This study aims to analyze the changes in the migration process regarding the availability, access, and food consumption of Venezuelan migrants in Bogotá, before and after their arrival. This study uses a naturalistic approach, with a convenience sample (n=15 families) who participated in in-depth semi-structured interviews about their experiences related to diet and nutrition, and the migratory process. Information was recorded, transcribed, and analyzed using grounded theory. Findings reflect that Venezuelan migrants leave the country due to severe lack of access to food which in turn affects the supply, acquisition, consumption, and nutritional status: “The main reason I left Venezuela was that I couldn´t get groceries like milk to feed my granddaughter. When that happened, I couldn´t stand it anymore.” After arrival in Colombia, dimensions of food and nutrition security, such as availability, physical and economic access, and consumption improved. However, families are still struggling to acquire basic food items. Households have access to a culturally adequate diet, but with insufficient nutritional quality, as noted by one participant: “The biggest difference is that in Venezuela you can´t get the groceries to feed your whole family with the salary that you get. Here in Bogota, you can buy cheap food, to feed the whole family”. After their arrival, migrants still face difficulties that include legal issues, finding a place to stay, employment, access to high-quality foods, and xenophobia. They have regained the freedom to choose the food they want to buy in a dignified and socially accepted way; two elements that were no longer possible in Venezuela.